1980
DOI: 10.1063/1.439793
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation in jet-cooled alkyl benzenes. I.Absorption spectra

Abstract: Fluorescence excitation spectra of a series of alkylbenzenes cooled in a supersonic free jet have been obtained for the first 1000 cm−1 region of the 1B2(ππ*)←1A1 ultraviolet absorption spectrum. The series includes all n-alkylbenzenes up to n-hexyl together with isopropyl- and tert-butylbenzene. As with toluene, the spectra in this region for all alkylbenzenes is found to be dominated by vibrations of five ring modes: 6a, 6b, 1, 12, and 18a. Three of these—the ’’system modes’’ (6b, 12, 18a)—are found to be la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
126
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(138 citation statements)
references
References 15 publications
11
126
1
Order By: Relevance
“…The S 1 electronic state of Tol-h 8 has been the focus of a number of studies in the past as described above. The vibrational structure observed here compares well to the early jet-cooled fluorescence excitation spectrum of Hopkins et al, 54 and also to the later spectra reported by both Hickman et al, 3 and Doyle et al 24 Good agreement is also seen with the (1 + 1) REMPI spectrum recently reported by Davies et al 41 and the (1 + 1) REMPI spectrum recorded by Gunzer and Grotemeyer. 43 It is noted that the relative intensities of several bands observed in the (1 + 1) REMPI spectrum reported in the present work differ from those observed in previous studies, particularly the origin band; this is attributed to the varying UV intensity across the wavenumber range of this spectrum.…”
Section: General Remarkssupporting
confidence: 79%
See 2 more Smart Citations
“…The S 1 electronic state of Tol-h 8 has been the focus of a number of studies in the past as described above. The vibrational structure observed here compares well to the early jet-cooled fluorescence excitation spectrum of Hopkins et al, 54 and also to the later spectra reported by both Hickman et al, 3 and Doyle et al 24 Good agreement is also seen with the (1 + 1) REMPI spectrum recently reported by Davies et al 41 and the (1 + 1) REMPI spectrum recorded by Gunzer and Grotemeyer. 43 It is noted that the relative intensities of several bands observed in the (1 + 1) REMPI spectrum reported in the present work differ from those observed in previous studies, particularly the origin band; this is attributed to the varying UV intensity across the wavenumber range of this spectrum.…”
Section: General Remarkssupporting
confidence: 79%
“…To higher and lower wavenumber there are weaker bands at 472.6 cm -1 and 451.8 cm -1 . In previous work, the assignment of the two most intense features to a Fermi resonance has been made; 3, 54 however, it is clear from other spectra, 24,54 and those presented here, that this region contains more than one contribution. Indeed, very recent time-resolved work (to be discussed further below), reports evidence for three contributions to the Fermi resonance.…”
Section: -500 CM -1 Fermi Resonance Regionmentioning
confidence: 84%
See 1 more Smart Citation
“…As in the lower wavenumber range, the overall appearance of the Tol-h 8 spectrum is similar to previously reported jet-cooled spectra. 3,20,21 There are several intense bands observed above 700 cm −1 , which have mainly been assigned to vibrations of a 1 symmetry; however, several combination bands of overall b 2 symmetry are observed, which owe their intensity to Herzberg-Teller coupling to the S 2 electronic state.…”
Section: A General Remarksmentioning
confidence: 99%
“…Two features are observed at 734.4 and 753.2 cm −1 for Tol-h 8 , which are labeled "M" and "N"; these have been previously assigned as a Fermi resonance between two ZOS vibrations. 21,22 The assignment of the higher wavenumber vibrational eigenstate has been long-established as having a major contribution from the M 10 fundamental, 3,21,22 while Hickman et al 3 assigned the other ZOS of the Fermi resonance to the M 18 M 19 combination. This assignment was based on the vibrational activity in the dispersed fluorescence spectrum recorded from these intermediate levels, and is expected to form the major contribution to the lower wavenumber component of the Fermi resonance.…”
Section: B 680-880 CM −1 Regionmentioning
confidence: 99%